HUBUNGAN STRES DAN KECANDUAN SMARTPHONE PADA SISWA KELAS X SMA NEGERI 5 SURAKARTA - Simon Simangunsong; Dian Ratna Sawitri (Jurnal EMPATI, 2017)
X grade students in the transition phase from junior high to high school are required to immediately adapt to the environment and master the lesson material that has never been before. With the sophistication of smartphones X-class students can solve problems they have to solve. This study aims to determine the relationship between stress with smartphone addiction in the class X students SMA Negeri 5 Surakarta. The hypothesis proposed is a significant positive relationship between stress with smartphone addiction in grade X students SMA N 5 Surakarta. The population of this study is the students of class X SMA Negeri 5 Surakarta as many as 300 students. A sample of 148 students consisting of 53 men and 95 women were obtained by cluster random sampling technique. The research instruments analyzed were Stress Scale (32 items; α = 0,88) and Smartphone Addiction Scale (29 items; α = 0,91). Simple regression analysis showed a positive and significant relationship between stress and subject matter smartphone addiction (rxy = 0.40; p <0.001). The results of this study indicate that the hypothesis proposed in this study accepted, ie there is a relationship between stress and addiction smartphones in the students of class X SMA Negeri 5 Surakarta. The data analysis shows R2 = 0.16 which explains that the contribution of stress to addiction of smartphone is 16% while the rest 84% is determined by other factor. Researchers provide suggestions for future researchers to conduct research into groups of subjects who have stress and high levels of smartphone addiction.